Antimicrobial Resistance in Escherichia coli and Enterococcal Isolates From Irrigation Return Flows in a High-Desert Watershed - Dungan, Robert S.; Bjorneberg, David L. (Frontiers in Microbiology, 2021)
Irrigation return flows (IRFs) collect surface runoff and subsurface drainage, causing them to have elevated contaminant and bacterial levels, and making them a potential source of pollutants. The purpose of this study was to determine antimicrobial susceptibility among Escherichia coli and enterococcal isolates that were collected from IRFs in a south-central Idaho watershed. Environmental isolates can be a potentially important source of antimicrobial resistance (AMR) and IRFs may be one way resistance genes are transported out of agroecosystems. Water samples were collected from 9 IRFs and 1 background site (canal water from Snake River) on a biweekly basis during 2018. Escherichia coli and enterococci were enumerated via a Most Probable Number technique, then subsamples were plated on selective media to obtain isolates. Isolates of E. coli (187) or enterococci (185) were tested for antimicrobial susceptibility using Sensititre broth microdilution plates. For E. coli, 13% (25/187) of isolates were resistant to tetracycline, with fewer numbers being resistant to 13 other antimicrobials, with none resistant to gentamicin. While 75% (141/187) of the E. coli isolates were pan-susceptible, 12 multidrug resistance (MDR) patterns with 17 isolates exhibiting resistance to up to 7 drug classes (10 antimicrobials). For the enterococcal species, only 9% (16/185) of isolates were pan-susceptible and the single highest resistance was to lincomycin (138/185; 75%) followed by nitrofurantoin (56/185; 30%) and quinupristin/dalfopristin (34/185; 18%). In addition, 13 enterococcal isolates belonging to E. faecalis, E. faecium, E. casseliflavus, and E. thailandicus, were determined to be MDR to up to 6 different antimicrobial drug classes. None of the enterococcal isolates were resistant to gentamycin, linezolid, tigecycline, and vancomycin.